The Quran And Science: An Analysis Of Compatibility - Prof. Dr. Matloob Ahmad , Dr Rana Amanullah , Muhammad Farhan Ur Rehman , Dr Wajid Ali , Muhammad Ajmal (Migration Letters, 2024)
The relationship between the Quran and science has been a topic of considerable interest and debate among scholars, scientists, and theologians. This paper explores the compatibility between the Quranic revelations and modern scientific discoveries. It examines various perspectives on how Quranic verses relate to scientific concepts, the historical context of Islamic scientific achievements, and the contemporary discourse surrounding this relationship. By analyzing specific Quranic verses and scientific theories, this paper aims to provide a nuanced understanding of the dialogue between faith and reason within the Islamic tradition. The exploration of th[1]e relationship between the Quran and modern science reveals a fascinating dialogue between faith and reason. This paper examines the compatibility of Quranic revelations with contemporary scientific discoveries, focusing on the historical context of Islamic contributions to science, the interpretation of specific Quranic verses in light of modern knowledge, and the current scholarly debates on the subject. By analyzing examples such as the creation of the universe, embryology, and the role of mountains, this study aims to illuminate how the Quran has inspired scientific thought and inquiry. The paper also addresses the challenges of interpreting religious texts through a scientific lens and advocates for a balanced approach that respects both the spiritual and empirical realms of knowledge.